ANALISIS PERMASALAHAN GURU BIOLOGI DALAM MELAKSANAKAN PROSES PEMBELAJARAN DARING DI MASA PANDEMI COVID-19 - Iskandar Muda; Syarifah Farissi Hamama; Maulida Maulida (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
The outbreak of the corona virus (Covid-19) as a pandemic requires learning to be carried out online (online), including in excellent high school in Banda Aceh which is one of the red zones in Aceh Province. This study aims to analyze the constraints of biology teachers at excellent High School Banda Aceh, in implementing online learning during the Covid-19 pandemic. This research was conducted at SMA Unggul Banda Aceh, with a total sample 19 biology teachers. The type of this research is a descriptive research with a quantitative approach. The data collection technique is done using a questionnaire in the form of google form. The research data were analyzed descriptively and quantitatively using the percentage formula. The results of the study showed there is a problem level at 72% (moderate category) experienced by the teacher during the implementation of online learning.